PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLANNING (SFE) BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP SWASTA SANTO PETRUS MEDAN - Sulistika Melani Sibarani; Ribka Kariani Sembiring; Frida Marta Argareta Simorangkir; Sinta Dameria Simanjuntak (STKIP Subang, 2025)
The research conducted at the Santo Petrus Medan Private Middle School in class VIII aims to describe the effect of the Student Facilitator and Eplaining (SFE) Cooperative Learning Model assisted by Geogebra on students' mathematical concept understanding ability on the material of straight line equations and line gradients and parallel lines and perpendicular lines. This study uses quantitative research with the experimental method. The population in this study were all students of class VIII of Santo Petrus Medan Private Middle School. The sampling technique was random sampling, selected students of class VIII-3 as the control class and students of class VIII-4 as the experimental class. The results of the pre-test and post-test were analyzed using normality and homogeneity tests. The results showed that the samples were normally distributed and homogeneous. Furthermore, an independent samples test was carried out, a significant value was obtained from the value of students' mathematical concept understanding ability between the control class and the experimental class with the results of the SPSS analysis, p <0.05, which means that there is an influence of the Student Facilitator and Eplaining (SFE) Cooperative Learning Model assisted by Geogebra on students' mathematical concept understanding ability. This can be seen from the test results with an average value of the control class of 25.19 and an average value of the experimental class of 75.58 with a t_count value = 14.81. The t_count value is higher than the t_table value of 1.99. So is rejected and is accepted. So it can be concluded that there is an influence of the Student Facilitator and Eplaining (SFE) Cooperative Learning Model assisted by Geogebra on students' mathematical concept understanding abilities with significant results. Keywords: